The causal effect of workplace violence on mental health and work-related outcomes: a cross-sectional study using propensity score matching - Javier A. Flores-Cohaila; Brayan Miranda-Chavez; Cesar Copaja-Corzo (PLoS ONE, 2025)
Introduction The prevalence of workplace violence in healthcare is 50–60%. While it has been linked to decreased job satisfaction, diminished quality of care, and economic burdens on healthcare systems, there are still major gaps. Previous studies ignored the Latin American perspective. Moreover, they neither offered causal evidence nor measured its impact on psychological outcomes. The objective was to evaluate the impact of workplace violence on psychological and work-related outcomes. Methods A secondary analysis of Peru’s 2016 National Healthcare Satisfaction Survey was conducted. This was a large-scale survey that used a stratified two-stage cluster sample design with a sample size of 5098 healthcare workers across all regions of Peru. Propensity score matching and Poisson regression models were used to assess the effect of self-reported workplace violence on outcomes, including depressive symptoms, burnout, sleep problems, work-life balance, and intention to quit. Results Among 4,951 healthcare workers, workplace violence prevalence was 41.91% higher in physicians (47.4%) than nurses (37.8%). WV had a moderate effect on sleep problems (aPR: 2.06, 95% CI: 1.45 to 2.97) and depressive symptoms (aPR: 1.65, 95% CI: 1.47–1.86). It showed small to moderate effects on burnout dimensions and intention to quit (aPR: 1.26, 95% CI: 1.13–1.41). The impact on work-life balance was small to negligible. Conclusions Workplace violence affects 4 in 10 Peruvian healthcare workers and is associated with adverse psychological and work-related outcomes. These findings highlight the need for improved reporting systems, targeted interventions such as policy development and training programs, and ensure adequate reporting systems.